SPECIAL FEATURES OF IMMUNE MORPHOLOGICAL FORMATION OF 9 DAYS OLD PIGLETS ORGANISM - Панікар, І. І.; Горальський, Л. П. (Scientific Progress & Innovations, 2013)
Partly activity of cells with markers CD79 (B-lymphocytes) in the lymph formations of lymphopoiesis and a high concentration of cells on the surface of the mucous membrane of the small part of the intestine shows the immaturity of their immune humoral factors of 9 days old piglets and the importance of maternal immune bodies in the life of newborn animals. The activity of lymphocytes with surface markers CD3 (lymphocyte tissue) is more expressed in the lymph nodes and lymphoid formations of the intestinal wall, feature of this process is the focal character.